The governance of activation - Berkel, Rik Van; Borghi, Vando (2008)
This article introduces the central topic of the thematic section of this issue: the governance of activation. it applies the concept of governance to new service provision models and considers why this is a relevant issue for social policy scholars. then, it provides a brief discussion of several aspects of the new service provision models that are being introduced all over Europe, where income protection schemes and activation policies are concerned. Finally, it introduces the other articles in the thematic section. - Reproduced.
Keywords: Public administration